Rapid Feedback Responses Parallel the Urgency of Voluntary Reaching Movements. (1st November 2021) - Poscente, Sophia V.; Peters, Ryan M.; Cashaback, Joshua G.A.; Cluff, Tyler
Highlights: Optimal feedback control proposes a link between voluntary and feedback control. We examined this link by altering the timing demands of human reaching movements. Reaching movements and perturbation responses were altered based on timing demands. Perturbation responses were influenced by the velocity of individual movements. Results highlight the link between voluntary actions and feedback control in humans. Abstract: Optimal feedback control is a prominent theory used to interpret human motor behaviour. The theory posits that skilled actions emerge from control policies that link voluntary motor control (feedforward) with flexible feedback corrections (feedback control). It is clear the nervous system can generate flexible motor corrections (reflexes) when performing actions with different goals. We know little, however, about shared features of voluntary actions and feedback control in human movement. Here we reveal a link between the timing demands of voluntary actions and flexible responses to mechanical perturbations. In two experiments, 40 human participants (21 females) made reaching movements with different timing demands. We disturbed the arm with mechanical perturbations at movement onset ( Experiment 1 ) and at locations ranging from movement onset to completion ( Experiment 2 ). We used the resulting muscle responses and limb displacements as a proxy for the control policies that support voluntary reaching movements. We observed an increase in the sensitivity of elbow and shoulder muscle responses and a reduction in limb motion when the task imposed greater urgency to respond to the same perturbations. The results reveal a relationship between voluntary actions and feedback control as the limb was displaced less when moving faster in perturbation trials. Muscle responses scaled with changes in the displacement of the limb in perturbation trials within each timing condition. Across both experiments, human behaviour was captured by simulations based on stochastic optimal feedback control. Taken together, the results highlight flexible control that links sensory processing with features of human reaching movements.